Maternal input to children with sex chromosome trisomies. Issue 5 (7th July 2020) - Zampini, Laura; Ferrante, Camilla; Silibello, Gaia; Dall'Ara, Francesca; Rigamonti, Claudia; Zanchi, Paola; Vizziello, Paola Giovanna; Lalatta, Faustina; Costantino, Maria Antonella
Abstract: Background: Although language difficulties are one of the most distinctive characteristics of the neuropsychological profile of children with sex chromosome trisomies (SCT), the analysis of the maternal input addressed to them is a neglected topic. Aims: The present study aims to analyse the lexical, morphosyntactic, and functional features of the input addressed to children with SCT comparing them with those of the input directed to typically developing children (TD). Methods & Procedures: Participants were 38 mothers and their 8‐month‐old children, 19 with SCT and 19 TD children. Maternal utterances, collected during video‐recorded play sessions, have been transcribed and coded. Outcomes & Results: No significant differences between groups have been found in the lexical and syntactic characteristics of maternal input. However, considering the input functional features, the proportion of directives and questions was significantly higher in the maternal input addressed to children with SCT than in the input addressed to TD children whereas the opposite pattern was found in the proportion of affect‐salient speech. Conclusions & Implications: The awareness of a possible delay in their children's language development could influence the way the mothers speak to them. In particular, the functional features of maternal input could be affected. Support groups for parents of children with SCT at the preverbal stage could be useful to reassure the mothers about their role in their children's language development. What this paper adds: What is already known on the subject: Studies in the literature identified a high percentage of language delays or impairments in children with SCT. To date, according to our knowledge, there are no studies that analyse the linguistic input addressed to these children. What this study adds: The lexical and syntactic features of maternal input addressed to 8‐month‐old children with SCT are adequate to the children's communicative skills. However, the mothers of children with SCT seem to provide additional scaffolding in their verbal input, using a lower proportion of affect‐salient speech and a higher proportion of questions. In addition, a higher proportion of directives suggests the use of a more demanding style. Clinical implications of this study: The awareness of possible language delays could influence the functional features of input leading mothers to use a more supportive and demanding input. Support groups for parents of children with SCT at the preverbal stage could be useful to reassure the mothers about their role in their children's language development.